Constitutive Equations and Processing Maps for 49MnVS3 Non-Quenched and Tempered Steel - Chen, Y.F.; Peng, X.D.; Xu, H.B.; Jiang, H.D.; Guan, G.H. (Проблемы прочности, 2014)
Flow stress variations of 49MnVS3 non-quenched and tempered steel are studied in isothermal compression tests on a Gleeble-1500D thermal simulated test machine at a deformation temperatures of 950, 1000, 1150, and 1200° C, and strain rates of 0.1, 1, 5, and 10 s⁻¹, with obtaining the strain hardening exponent n and deformation activation energy Q of the alloy. Thus, the constitutive equations and processing maps of compression flow behavior for 49MnVS3 non-quenched and tempered steel at high temperatures are established. It shows that the peak stress is shownto significantly reduced with a decrease in the strain rate and increase in deformation temperature when the alloy deforms at high temperature, and the deformation activation energy is 350.98 kJ/mol. When the true strain of 49MnVS3 non-quenched and microalloyed steel high-temperature deformation is 0.5, the optimum process parameters of the alloy are determined to be 1150–1200° C for the deformation temperature and 2–10 s⁻¹ for the strain rate, based on the criterion that the process parameters of higher power dissipation efficiency values should be chosen in the dynamic recrystallization region as the best processing technology.